UVA Radiation Is Beneficial for Yield and Quality of Indoor Cultivated Lettuce - Chen, Yongcheng; Li, Tao; Yang, Qichang; Zhang, Yating; Zou, Jie; Bian, Zhonghua; Wen, Xiangzhen (Frontiers in Plant Science, 2019)
Understanding the wavelength dependence of plant responses is essential for optimizing production and quality of indoor plant cultivation. UVA is the main component of solar UV radiation, but its role on plant growth is poorly understood. Here, two experiments were conducted to examine whether UVA supplementation is beneficial for indoor plant cultivation. Lettuce (Lactuca sativa L. cv. ‘Klee’) was grown under mixed blue, red and far-red light with photon flux density (PFD) of 237μmol m-2 s-1 in the growth room; photoperiod was 16 h. In the first experiment, three UVA intensities with peak wavelengths at 365 nm were used: 10 (UVA-10), 20 (UVA-20) and 30 (UVA-30) μmol m-2 s-1, respectively. In the second experiment, 10 μmol m-2 s-1 UVA radiation were given for 5 (UVA-5d), 10 (UVA-10d) and 15 (UVA-15d) days before harvest on day 15, respectively. Compared with control (no UVA), shoot dry weight was increased by 27%, 29% and 15% in the UVA-10, UVA-20, and UVA-30 treatments, respectively, which correlated with 31% (UVA-10), 32% (UVA-20) and 14% (UVA-30) larger leaf area. Shoot dry weight under the treatments of UVA-5d, UVA-10d and UVA-15d was increased by 18%, 32% and 30%, respectively, and leaf area was increased by 15-26%. For both experiments, UVA radiation substantially enhanced secondary metabolites accumulation, e.g. anthocyanin and ascorbic acid contents were increased by 17-49% and 47-80%, respectively. Moreover, plants grown under the UVA-30 treatment were stressed, as indicated by lipid peroxidation and lower maximum quantum efficiency of photosystem II photochemistry (Fv/Fm). We conclude that UVA supplementation not only stimulates biomass production in controlled environments, but also enhances secondary metabolite accumulation.